In vitro regeneration of Dioscorea alata with anthocyanin and antimicrobial activity / Sakinah Abdullah - Sakinah , Abdullah (2020)
An efficient protocol was developed for rapid propagation and regeneration of the Dioscorea alata L. locally known as ‘ubi badak’ because of their rhinoceros-shaped tubers. In the present study, direct and indirect regeneration were induced to produce plantlets of Dioscorea alata L. For direct regeneration explants (leave, stem and node) were cultured on MS media supplemented with various combinations and concentrations of BAP and NAA to induce microshoots and roots formation. The optimum medium for microshoots formation was MS medium supplemented with 1.0 mg/l BAP and 0.5 mg/l NAA with the number of microshoot is 23.07±0.44 from node explant. While for root formation, MS medium supplemented with 2.0 mg/l NAA is the optimum medium with mean number of roots formation 17.40±0.58. For indirect regeneration, microtubers formation, callus induction, somatic embryogenesis and synthetic seeds production were studied. MS medium supplemented with 1.0 mg/l NAA and1.0 mg/l BAP, is the best medium for microtubers formation with 15.57±0.18 mean number of microtubers. MS medium supplemented with 1.0 mg/l BAP and mg/l 1.0 NAA was the best medium for microtubers germination with percentage of germination 76.67±0.08 %. Callus induction was obtained on MS media supplemented with various concentration of 2,4-D, NAA, TDZ, BAP, myo-inositol and activated charcoal. Node explant cultured in MS medium supplemented with 2.0 mg/l 2,4-D and 1.0 mg/l BAP added with 0.5 mg/l myo-inositol was the best condition for optimum callus production. Callus were then identified whether it is embryogenic or non embryogenic using double staining method. Embryogenic callus was stained in red and non embryogenic callus was stained in blue. Embryogenic callus was then subculture onto solid and liquid somatic embryos induction medium. MS medium supplemented with 2.5 mg/l 2,4-D combine with 1.0 mg/l BAP is the best medium for somatic embryos formation from 0.5 cm of embryogenic callus. Synthetic seeds were created by encapsulated propagules (microshoots, node and stem) with 16 different solution of sodium alginate and Calcium chloride dehydrate. In this study, propagules were successfully encapsulated in 2.0 to 5.0 % sodium alginate solution and harden in 25.0 to 100.0 mM Calcium chloride dehydrate solution. The beads varied morphologically with respect to texture, shape and transparency with different combinations of sodium alginate solution and calcium chloride. 3% sodium alginate harden in 100 µM Calcium chloride dehydrate was found to be the best encapsulation solution. Complete plantlets obtained from direct and indirect regeneration were then transferred to greenhouse. Plantlets response positively when acclimatized in garden soil (combination of black soil and red soil at ratio 2 to 1) with 93.33±0.09 % of survival rate. Callus exposed to different photoperiod produced different amount of anthocyanin. The total anthocyanin content was calculated using pH differential method. The highest (295.21 ± 0.20 mg cya-3-glu / 100 g FW) anthocyanin content was obtained from callus exposed to 16 hours light and 8 hours dark. Antimicrobial activity studies reveal that this plant response positively against bacteria (Staphylococcus aureus, Staphylococcus epidermis, Escherichia coli and Salmonella sp.) and fungi (Penicillium sp., and Mucor sp.) negative effect against Aspergilus nigerand Fusarium sp.